Policy Inhibitors of Petrochemical Product Export Development - Najafpour, Hoda; Shirkhodaie, Meysam; Aghajani, Hassanali; Soltanzadeh, Javad (Business, Marketing, and Finance Open, 2025)
Exports play a direct role in the economic development of a country. In the turbulent and competitive global environment, having a reliable approach to achieving short-term and long-term objectives in companies can support their growth and development. The aim of this study is to examine the inhibitors of petrochemical export development from the perspectives of industrial, trade, and technological policies. This research is applied in nature and has been conducted using the qualitative method of thematic analysis. Data collection tools included past documents and records as well as interviews. In this approach, 32 published articles from reputable domestic and international scientific-research databases were reviewed, and interviews were conducted with 16 experts and international consultants in the petrochemical industry, researchers from the Parliament Research Center, and policymakers. The sampling method was purposive, and the selection of interviewees followed a snowball sampling approach. Qualitative data were analyzed using thematic analysis. In the qualitative data analysis, 132 codes were identified, which, after merging similar codes, resulted in 81 final codes. These were classified into 14 similar concepts and ultimately grouped into 7 main themes. In the quantitative phase, a questionnaire was designed, and 10 experts were selected based on the judgmental sampling method to prioritize the identified themes using the DEMATEL method. The questionnaire analysis results indicated that "weaknesses in governance policies" had the highest impact among all factors. Furthermore, "weaknesses in governance policies," "structural and institutional issues," and "weaknesses in the supervisory and evaluation system" were identified as causal inhibitors.